Le relative appositive nella costruzione del testo - Ferrari, Angela (Cuadernos de Filología Italiana, 2006)
In this paper, written in the framework of Text Linguistics, the Author examines independent appositive relations. Specifically, she defines their contribution to the construction of the architecture of discourse through a comparison with other denotatively similar linguistic structures. In addition, by employing an analysis of the morphosyntactic, intonational and punctuation levels, the Author identifies the criterion that differenciates restrictive relatives from appositive relatives. Appositive relatives form an independent minimal text unit that can work either at the informative or at the utterance level. Through this comparison with other linguistic structures, the Author then determines the specific contribution of appositive relative clauses to the construction of text in its thematic, logico-argumentative and illocutive- interactive dimensions. In doing so, she is particularly attentive to the different interpretations that arise from variations in distribution and punctuation.